Physician and Patient Preferences for the Treatment of Metastatic Castration-Sensitive and Castration-Resistant Prostate Cancer: A Best-Worst Scaling Study in Japan - Takahiro Kimura; Noriko Takahashi; Keiko Asakawa; Atsushi Saito; Takeshi Mitomi; Takumi Lee; Mika Matsumura (Oncology and Therapy)
Abstract Introduction Despite many prostate cancer (PC) treatment options in Japan, physicians’ and patients’ preferences in metastatic castration-sensitive PC (mCSPC) and castration-resistant PC (CRPC) are unclear. Methods For this cross-sectional study, an online questionnaire survey based on the best–worst scaling (profile case) approach was designed. Physicians’ and patients’ questionnaires, comprising six attributes (efficacy, safety, target patients, dosage, administration, and medical expenditures), had 24 and 26 items for mCSPC and CRPC surveys, respectively. Four items were presented during each session; respondents selected the “most important” and “least important” among these. The objective was to elicit attributes important for treatment and their relative importance levels among physicians and patients and to explore similarities and differences in choices. Multinomial logit and hierarchical Bayesian models were applied, and preferences were presented as relative importance and utility values. Results Responses of 177 physicians (urologists: 173; oncologists: 4) and 292 patients (mCSPC: 94; CRPC: 198) were analyzed. Most patients with CRPC (63.1%) had no metastases. Efficacy was the most important attribute overall. Physicians considered patient survival the most important among efficacy items (11.1%), whereas patients with mCSPC prioritized prevention of metastases spread (9.7%) and prostate-specific antigen (PSA) elevation (9.3%). In CRPC, both physicians and patients prioritized prevention of metastasis development or its spread (physicians: 9.6%; patients: 8.3%) and PSA elevation (physicians: 9.3%; patients: 7.9%). After efficacy, physicians prioritized items related to target patients (cardiovascular disorders; mCSPC: 4.8%; CRPC: 3.4%), whereas patients prioritized safety (mCSPC: falls or fractures [5.6%]; CRPC: liver dysfunction [4.7%]). Patients with mCSPC were also concerned about rising medical expenditures (5.4%). Conclusion Treatment efficacy was the most important attribute for both physicians and patients in Japan in mCSPC and CRPC settings, although their preferences differed in priority based on outcomes. These findings may be useful to improve shared decision-making for PC treatment in Japan.